9(X-3)/3=6(X+2)/12

Simple and best practice solution for 9(X-3)/3=6(X+2)/12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(X-3)/3=6(X+2)/12 equation:


X in (-oo:+oo)

(9*(X-3))/3 = (6*(X+2))/12 // - (6*(X+2))/12

(9*(X-3))/3-((6*(X+2))/12) = 0

(9*(X-3))/3+(-1/2)*(X+2) = 0

(9*(X-3))/3-1/2*(X+2) = 0

(9*(X-3))/3+(-1/2*3*(X+2))/3 = 0

9*(X-3)-1/2*3*(X+2) = 0

15/2*X-30 = 0

(15/2*X-30)/3 = 0

(15/2*X-30)/3 = 0 // * 3

15/2*X-30 = 0

15/2*X-30 = 0 // + 30

15/2*X = 30 // : 15/2

X = 30/15/2

X = 4

X = 4

See similar equations:

| -4y^2=24y | | -7(x-7)-6=43 | | x^2/3-x/2-35/6=0 | | 3y+x=4x+-3 | | 16/-11=n/29 | | -5(3T-5)+2T=6T-5 | | 37/y=7/3 | | -2cos^2x+5=5sinx | | p^2xP^6= | | 3(2X+3)=6X+9 | | (3x+8/5)-7=-x+9 | | 3(p+6q-14)= | | 3x+8/5-7=-x+9 | | 7x+9=7(x+8) | | 4/0.8=0.3/w | | 0.50X+0.35(70)=36.5 | | 0.9/0.5=z/4.5 | | 2x^2-0=14 | | 45/50=m/100 | | x/7=8/21 | | (x-5)(x^2+2x+5)= | | 6y+2-8y=3-2y-10 | | =-2(7+6n) | | -4(x-1)-(2-x)=-6 | | -5/9y-(y-5/6)=1/54(y-6) | | 16x+8y=-17 | | 8n+10-2n=3n-2+5n | | 8n+10-22=3n-2+5n | | -2x-10=4+5x | | -3-2x=18 | | 8(3w-7)=6(4w+5) | | -15+2m=-11 |

Equations solver categories